Preparation method and application of N and P modified Ti3C2Tx electrode material

By forming Ti-P, Ti-O-P, Ti-N bonds on the surface of Ti3C2Tx material, and modifying materials with N and P compounds, the problems of material re-stacking and side reactions are solved, and the high magnification and long-life performance of lithium-ion batteries are improved. , achieving high power density and high rate performance of the material.

CN119208596AActive Publication Date: 2024-12-27UNIV OF SCI & TECH BEIJING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411145654.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-27
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The existing Ti3C2Tx material is re-stacked in lithium-ion batteries due to interlayer van der Waals forces and hydrogen bonds, which hinders the diffusion of lithium ions, and the surface end group structure reacts sideways with the electrolyte, deteriorating high-rate electrochemical performance.

Method used

Through the pyrolysis of N and P compounds, Ti-P, Ti-O-P, and Ti-N bonds are formed on the surface of Ti3C2Tx material, the charge distribution on the surface of the material is optimized, the electronic cloud structure is adjusted, and the N and P functional groups are constructed by solvothermal method to improve the electrical energy of the material. Chemical properties.

Benefits of technology

It significantly improves the high magnification and long-life lithium storage performance of the material, enhances the lithium ion diffusion performance, improves the first discharge and charging specific capacity, and improves the cycling stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208596A_ABST
    Figure CN119208596A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an N and P modified Ti < 3 > C < 2 > T < x > electrode material, and relates to the field of lithium ion battery negative electrode materials. The preparation method comprises the following steps: 1) uniformly dispersing a prepared Ti < 3 > C < 2 > T < x > material in deionized water, and then performing ultrasonic treatment to obtain a uniform Ti < 3 > C < 2 > T < x > dispersion liquid; 2) adding a compound solution containing N and P into the dispersion liquid, and stirring and mixing; and (3) pouring the mixed solution obtained in the step (2) into a polytetrafluoroethylene reaction kettle lining, carrying out solvothermal reaction, cooling, carrying out centrifugal washing on the obtained sample by adopting deionized water, and carrying out vacuum drying to obtain the N, P-coated Ti3C2Tx material. According to the method, one of urea phosphate, amino trimethylene phosphonic acid and N-bis (phosphine hydroxymethyl) glycine is used as an N and P source, and N and P functional groups are constructed on the surface of the Ti3C2Tx material by adopting a solvothermal method, so that charge distribution on the surface of the material is effectively regulated and controlled, transmission and diffusion of carriers at a material interface are accelerated, the material structure is stabilized, and the lithium ion diffusion performance of the material is improved; the application of the Ti3C2Tx material in the aspect of the negative electrode of the lithium ion battery is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery negative electrode materials, and specifically relates to a method for rapidly hydrothermally modifying Ti3C2T using N and P compounds. x Methods for characterizing surface functional groups of materials and their applications in lithium-ion batteries. Background Art

[0002] Rechargeable lithium-ion batteries (LIBs) have the advantages of high energy density and long cycle life. They are the most promising electrochemical energy storage devices after traditional lead-acid, nickel-iron and nickel-metal hydride batteries, and have broad application prospects in rail transportation, electric vehicles, mobile phones, aerospace and other fields. Electrode materials are the key factors that determine the overall performance of batteries, and have an important impact on issues such as electrochemical potential and reaction kinetics. Improving the specific capacity of negative electrode materials is the key to improving the energy density and power density of lithium-ion batteries.

[0003] MXene material is a new type of two-dimensional layered material with the general formula of M n+1 X n T x (n=1~4), where M represents a transition metal (Sc, Ti, Zr, Hf, V, Nb, Cr, Mo, etc.), X represents carbon or nitrogen, and T x The MXene material has good electronic conductivity due to the presence of the conductive metal carbide center layer. In addition, the surface of MXene can be modified by using functional groups. The phosphorus and sulfur functional groups formed by surface functional group modification provide abundant active sites for lithium ion storage, which is beneficial to improve the specific capacity of the material. At the same time, the large specific surface area and nanolayer structure of MXene are conducive to the diffusion of ions between layers, improving the material rate performance and volume specific capacity. However, MXenes are similar to two-dimensional graphene structures. The interlayer van der Waals forces and hydrogen bonds cause the material to restack during long cycles, thereby hindering the diffusion and migration of lithium ions between material layers. At the same time, the complex surface end group structure of the material will react with the electrolyte, resulting in irreversible consumption and decomposition of the electrolyte, and passivating the surface structure of the material, hindering the adsorption and diffusion of carriers on the surface of the material, and seriously deteriorating the high-rate electrochemical performance of the material. Summary of the invention

[0004] The present invention is to improve Ti3C2T x The electrochemical stability and rate performance of the material are proposed by using thermal decomposition of N and P organic matter in Ti3C2T xThe method of N and P co-doping on the surface of the material is to generate chemical bonds such as PO bonds and NH bonds in P2O7 and NH2 functional groups after pyrolysis of N and P compounds and interact with Ti-O bonds, Ti-OH bonds, Ti-F bonds, etc. in the material body. x Ti-P, Ti-OP, Ti-N bonds are formed on the surface of the material to achieve Ti3C2T x The surface functional groups of the materials are modified to optimize the surface charge distribution of the materials and improve the electrochemical performance of the materials. The present invention introduces a variety of N and P functional groups in the synthesis to adjust the surface electron cloud structure of the materials, effectively realizing the Ti3C2T x High-rate and long-life lithium storage applications of materials.

[0005] The present invention is achieved through the following technical solutions:

[0006] A N and P modified Ti3C2T x The method for preparing an electrode material is characterized by comprising the following steps:

[0007] (1) Prepare Ti3C2T x The material was evenly dispersed in deionized water and ultrasonicated to obtain uniform Ti3C2T x Dispersion liquid;

[0008] (2) Dissolve a certain amount of N and P compounds in deionized water and obtain a uniform N and P compound solution under magnetic stirring;

[0009] (3) Slowly adding corresponding volumes of N and P compound solutions to the dispersion, and mixing the N and P compound solutions and the dispersion thoroughly and evenly under magnetic stirring conditions;

[0010] (4) The uniform dispersion obtained in step (3) is poured into a polytetrafluoroethylene reactor liner and subjected to solvent thermal reaction at a certain temperature for a certain period of time, and then the product is centrifuged and washed with deionized water, and further vacuum dried to obtain the target product N,P@ Ti3C2T x Material.

[0011] Furthermore, the volume of deionized water in step (1) is 120 mL, and the dispersed Ti3C2T x The material mass is 30 mg.

[0012] Furthermore, the volume of deionized water in step (2) is 120 mL, and the dissolved N and P compounds and the Ti3C2T dispersed in step (1) are x The material mass ratios are 5:1, 10:1 and 15:1.

[0013] Furthermore, the volume of the corresponding solution added in step (3) is 120 ml, and the N, P compound solution is one of urea phosphate solution, aminotrimethylenephosphonic acid solution, and N-bis(phosphinoylmethyl)glycine solution.

[0014] Furthermore, in the step (4), the solvent thermal reaction temperature is 100-140°C, the solvent thermal reaction time is 4-8 h, the vacuum drying temperature is 80°C, and the vacuum drying time is 12 h.

[0015] According to the method described above, N and P modified Ti3C2T x Electrode material application and lithium electronic battery negative electrode, characterized in that the Ti3C2T x The N and P functional groups are constructed on the surface of the material, which effectively regulates the charge distribution on the surface of the material, accelerates the transmission and diffusion of carriers at the interface of the material, stabilizes the material structure, and improves the lithium ion diffusion performance of the material. The lithium-ion battery assembled using this material has greatly improved the initial discharge capacity and charge capacity, promoting the Ti3C2T x Application of materials in negative electrodes of lithium-ion batteries.

[0016] The mechanism of the present invention is:

[0017] The urea phosphate (chemical formula is CO(NH2)2·H3PO4) and aminotrimethylenephosphonic acid (chemical formula is C3H 12 NO9P3), N-bis(phosphinoylmethyl)glycine (chemical formula is C4H 11 NO8P2), in the solvent thermal reaction, when the system temperature reaches above 120℃, the above N and P compounds begin to decompose. When the temperature reaches above 160℃, the reaction is relatively rapid. During the reaction, the N and P compound molecules will decompose to produce substances containing P2O7, NH2, etc. The PO bonds and NH bonds in the decomposition products will react with Ti3C2T x The C-Ti-O or C-Ti-OH bonds in the outer Ti atomic layer of the material react to form chemical bonds such as Ti-OP, Ti-P, Ti-N, and P=O. The chemical bonds such as Ti-OP, Ti-P, and Ti-N are beneficial to stimulate the charge transfer on the surface of the material, expand the interlayer spacing of the material, and improve the electrochemical kinetics of the material, thereby realizing Ti3C2T x High power density applications of materials.

[0018] The innovation of the present invention lies in:

[0019] The urea phosphate, aminotrimethylenephosphonic acid and N-bis(phosphinohydroxymethyl)glycine used in the present invention are commonly used phosphate fertilizers and industrial additives. The above three substances are used as nitrogen and phosphorus sources. xThe introduction of -N and -P end groups on the surface of the material forms Ti-OP, Ti-P, and Ti-N chemical bonds, which can expand the material interlayer spacing, improve the electronic structure of the material surface, provide more lithium ion adsorption sites, and increase the lithium storage capacity of the material; at the same time, the introduction of functional groups containing N and P elements can also provide support for the material during the cycle process, effectively improving the heavy stacking problem in the long cycle of the material, so that the modified material has excellent rate performance and cycle stability.

[0020] The method of the present invention uses one of urea phosphate, aminotrimethylenephosphonic acid and N-bis(phosphinohydroxymethyl)glycine as the N and P sources, and adopts a solvothermal method to prepare Ti3C2T x The N and P functional groups are constructed on the surface of the material, which effectively regulates the charge distribution on the surface of the material, accelerates the transmission and diffusion of carriers at the interface of the material, stabilizes the material structure, and improves the lithium ion diffusion performance of the material. The lithium-ion battery assembled using this material has greatly improved the initial discharge capacity and charge capacity, promoting the Ti3C2T x Application of materials in negative electrodes of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the X-ray diffraction (XRD) spectrum of the materials prepared in Example 2 and the comparative example.

[0022] Figure 2 The initial Ti3C2T prepared in comparative example x Scanning electron microscope (SEM) image of the material.

[0023] Figure 3 It is N,P-Ti3C2T prepared in Example 2 x Scanning electron microscope (SEM) image of the material.

[0024] Figure 4 (a) is N,P-Ti3C2T prepared in Example 2 x Phosphorus element spectrum (EDS) diagram of the material, Figure 4 (b) is N,P-Ti3C2T prepared in Example 2 x Nitrogen element energy spectrum (EDS) diagram of the material.

[0025] Figure 5 It is a performance diagram of the first charge and discharge curves of the materials prepared in Example 1, Example 2, Example 3 and Comparative Example 11.

[0026] Figure 6 It is a half-cell low current density cycle performance diagram of the materials prepared in Example 2 and the comparative example.

[0027] Figure 7 It is a half-cell high current density cycle performance diagram of the materials prepared in Example 2 and the comparative example.

[0028] Figure 8 It is a half-cell rate performance diagram of the materials prepared in Example 2 and the comparative example.

[0029] Fig. 9 It is a half-cell rate performance diagram of the materials prepared in Example 9 and the comparative example.

[0030] Fig.10 It is a half-cell rate performance diagram of the materials prepared in Example 10 and the comparative example. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the embodiments and drawings, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0033] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0034] (2) Disperse 1.5 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0035] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0036] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 120°C for 6 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0037] Embodiment 2: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0038] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0039] (2) Disperse 3 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0040] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0041] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 120°C for 6 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0042] Embodiment 3: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0043] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0044] (2) 4.5 g of urea phosphate was uniformly dispersed in 120 mL of deionized water and stirred with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0045] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0046] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 120°C for 6 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0047] Example 4: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0048] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0049] (2) Disperse 3 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0050] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0051] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed at 100°C for hydrothermal reaction for 6 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0052] Example 5: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0053] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0054] (2) Disperse 3 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0055] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0056] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed at 140°C for hydrothermal reaction for 6 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0057] Example 6: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0058] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0059] (2) Disperse 3 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0060] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0061] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 160°C for 6 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0062] Example 7: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0063] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0064] (2) Disperse 3 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0065] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0066] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 120°C for 4 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0067] Example 8: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0068] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0069] (2) Disperse 3 g of urea phosphate evenly in 120 mL of deionized water and stir with a magnetic stirrer for 30 min to obtain a urea phosphate solution;

[0070] (3) Slowly add the urea phosphate solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0071] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed at 160°C for hydrothermal reaction for 8 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0072] Example 9: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0073] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0074] (2) 3 g of aminotrimethylenephosphonic acid was uniformly dispersed in 120 mL of deionized water, and stirred with a magnetic stirrer for 30 min to obtain an aminotrimethylenephosphonic acid solution;

[0075] (3) Slowly add the aminotrimethylenephosphonic acid solution prepared in (2) into the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0076] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 120°C for 8 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0077] Embodiment 10: A method for preparing a N and P modified Ti3C2Tx electrode material, comprising the following steps:

[0078] (1) 0.3 g of prepared Ti3C2T x The material was evenly dispersed in 120 mL of deionized water and ultrasonicated for 30 min to obtain a uniform Ti3C2T x Dispersion liquid;

[0079] (2) 3 g of N-bis(phosphinohydroxymethyl)glycine was uniformly dispersed in 120 mL of deionized water and stirred with a magnetic stirrer for 30 min to obtain an N-bis(phosphinohydroxymethyl)glycine solution;

[0080] (3) Slowly add the N-bis(phosphinothiomethyl)glycine solution prepared in (2) to the Ti3C2T x The solution and the dispersion were then mixed thoroughly using a magnetic stirrer;

[0081] (4) The dispersion obtained in step (3) was uniformly transferred to four polytetrafluoroethylene lined reactors, and then the reactors were placed in a hydrothermal reaction at 120°C for 8 h. The hydrothermal product was filtered and washed with deionized water, and then vacuum dried at 80°C for 12 h to obtain the target product N,P@ Ti3C2T x Material.

[0082] Comparative example: a Ti3C2T x The method for preparing the material comprises the following steps:

[0083] (1) Slowly add 2 g of Ti3AlC2 precursor into 32 mL of 40% hydrofluoric acid and stir at room temperature for 48 h.

[0084] (2) After the reaction is complete, centrifuge with deionized water and wash at 10,000 r min –1 The reaction mixture was centrifuged at 3500 r min for 5 min to remove the participating acids and reaction products. –1 Centrifuge at 500 rpm for 5 min and repeat several times until the pH value of the supernatant is 6;

[0085] (3) The precipitate was vacuum filtered and washed with deionized water, and then vacuum dried at 80 °C for 12 h to obtain Ti3C2T x Material.

[0086] Test example:

[0087] Half-cell assembly: N,P@ Ti3C2T prepared in Examples 1, 2, and 3 x Materials and Comparative Examples Ti3C2T x The materials were slurried and coated with Super P and PVDF in a mass ratio of 80:10:10, and punched out to obtain electrode sheets with a diameter of 12 mm. Metallic lithium was used as the negative electrode, and the LIB-111 high-voltage resistant electrolyte of Suzhou Duoduo Chemical Technology Co., Ltd. was used as the electrolyte. The half-cell was assembled in an argon atmosphere glove box.

[0088] Charge and discharge test: The voltage range of the button half-cell charge and discharge is 3.0-0.01 V. Before the cycle test, it was activated three times with a current density of 15 mA / g, and then the charge and discharge cycle test was carried out at a current density of 150 mA / g and 750 mA / g in the same voltage range. All electrochemical performance tests were carried out at 30 ℃.

[0089] Figure 1 The XRD patterns of Example 2 and the comparative example show that the P-modified Ti3C2T x The sample still has good Ti3C2T x Layered structure, where the (002) crystal plane diffraction peak corresponds to the layer structure of the sample along the c-axis direction. After modification, the (002) peak position of the sample shifts to the left, indicating that the material interlayer spacing increases, which promotes the interlayer diffusion of lithium ion materials and is beneficial to the improvement of the electrochemical performance of the modified sample.

[0090] contrast Figure 2 , 3 The SEM images corresponding to the comparative example and Example 2 show that the P-modified material still has an accordion-like structure under the scanning electron microscope ( Figure 3 );at the same time Figure 4 The EDS test of nitrogen and phosphorus elements in Example 2 shows that nitrogen and phosphorus elements are uniformly distributed in N,P-Ti3C2Tx, indicating that nitrogen and phosphorus elements are successfully incorporated into the material.

[0091] Figure 5 It is the first cycle charge and discharge curve after assembling half-cells of Example 1, Example 2, Example 3 and the comparative example. It can be seen that the first charge and discharge specific capacities of the materials of Example 2 and Example 3 are significantly improved, wherein the first discharge specific capacity of Example 2 is 799.8 mAh / g, and the charging specific capacity is 342.1 mAh / g, the first discharge specific capacity of Example 3 is 788.8 mAh / g, and the charging specific capacity is 309.2 mAh / g, while the first discharge specific capacity of the comparative example is 459.6 mAh / g, and the charging specific capacity is only 251.1 mAh / g.

[0092] Figure 6 The figure is a cycle performance diagram of the half-cell assembled in Example 2 and the comparative example after 300 cycles at a current density of 150 mA / g. After 300 cycles, the capacity of Example 2 is 193.1 mAh / g, and the capacity retention rate is 97.0%, while the capacity of the comparative example is only 117.3 mAh / g after 300 cycles, and the capacity retention rate is 94.7%. Figure 7The figure is a cycle performance diagram of the half-cells assembled in Example 2 and the comparative example after 500 cycles at a current density of 750 mA / g. After 500 cycles, the capacity of Example 2 is 151.9 mAh / g, and the capacity retention rate is 97.7%, while the capacity of the comparative example is only 78.7 mAh / g after 500 cycles, and the capacity retention rate is only 87.0%. Figure 8 1 is a rate performance diagram of half cells assembled from Example 2 and the comparative example. Example 2 has a charge capacity of 160.9 mAh / g at a current density of 3000 mA / g, while the comparative example only has a charge capacity of 54.8 mAh / g.

[0093] Fig. 9 The rate performance diagram of the half-cell assembled by Example 9 and the comparative example shows that Example 9 exhibits a specific charge capacity of 235.3 mAh / g at a current density of 30 mA / g, which is significantly higher than 194.4 mAh / g of the comparative example. Example 2 has a specific charge capacity of 126.9 mAh / g at a current density of 3000 mA / g, while the comparative example only exhibits a specific charge capacity of 54.8 mAh / g. Fig.10 : is the rate performance diagram of the half-cell assembled by Example 10 and the comparative example. Example 10 exhibits a charge capacity of 246.6 mAh / g at a current density of 30 mA / g, which is significantly higher than 194.4 mAh / g of the comparative example.

[0094] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A N and P modified Ti3C2T x The method for preparing an electrode material is characterized in that: The following steps are involved: (1) Prepare Ti3C2T x The material was evenly dispersed in deionized water and ultrasonicated to obtain uniform Ti3C2T x Dispersion liquid; (2) Dissolve a certain amount of N and P compounds in deionized water and obtain a uniform N and P compound solution under magnetic stirring; (3) Slowly adding corresponding volumes of N and P compound solutions to the dispersion, and mixing the N and P compound solutions and the dispersion thoroughly and evenly under magnetic stirring conditions; (4) The uniform dispersion obtained in step (3) is poured into a polytetrafluoroethylene reactor liner and subjected to solvent thermal reaction at a certain temperature for a certain period of time, and then the product is centrifuged and washed with deionized water, and further vacuum dried to obtain the target product N,P@ Ti3C2T x Material.

2. A N, P modified Ti3C2T according to claim 1 x The method for preparing an electrode material is characterized in that: The volume of deionized water in step (1) is 120 mL, and the dispersed Ti3C2T x The material mass is 30 mg.

3. A N, P modified Ti3C2T according to claim 1 x The method for preparing an electrode material is characterized in that: The volume of deionized water in step (2) is 120 mL, and the dissolved N and P compounds are mixed with the Ti3C2T dispersed in step (1). x The material mass ratios are 5:1, 10:1 and 15:

1.

4. A N, P modified Ti3C2T according to claim 1 x The method for preparing an electrode material is characterized in that: The volume of the corresponding solution added in step (3) is 120 ml, and the N, P compound solution is one of urea phosphate solution, aminotrimethylenephosphonic acid solution, and N-bis(phosphinoylmethyl)glycine solution.

5. A N, P modified Ti3C2T according to claim 1 x The method for preparing an electrode material is characterized in that: In the step (4), the solvent thermal reaction temperature is 100-140°C, the solvent thermal reaction time is 4-8 h, the vacuum drying temperature is 80°C, and the vacuum drying time is 12 h.

6. N, P modified Ti3C2T prepared by the method according to claim 1 x The electrode material is applied to the negative electrode of a lithium-ion battery, characterized in that: Solvothermal method was used to prepare Ti3C2T x Material surface construction The N and P functional groups effectively regulate the charge distribution on the material surface, accelerate the transmission and diffusion of carriers at the material interface, stabilize the material structure, and improve the lithium ion diffusion performance of the material. The lithium-ion battery assembled using this material has greatly improved the initial discharge capacity and charge capacity, promoting the Ti3C2T x Application of materials in negative electrodes of lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of nitrogen-phosphorus double-doped hollow carbon nanotube

    CN107262127A

  • Modified N and P co-doped lithium titanate negative electrode material and preparation method thereof

    CN111403724A

  • Heteroatom doped mesoporous carbon / tin composite negative electrode material for lithium ion battery as well as preparation method and application of heteroatom doped mesoporous carbon / tin composite negative electrode material

    CN112599739A

  • Method for obtaining N and P co-doped graphite felt electrode

    CN116072891A

  • Preparation method and application of organic phosphoric acid molecule functionalized Ti3C2Tx electrode material

    CN117594777A